SISTEM INFORMASI PENOMORAN SURAT (STUDI KASUS FAKULTAS TEKNIK UNIVERSITAS LAMBUNG MANGKURAT) - Dwi Hastuti (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2016)
Letter is one of the communication media has an important role. Besides having the function of a messenger, the letter also become one of the important documents for an organization. Because all forms of official communication must be submitted by mail. Engineering Faculty of Lambung Mangkurat University is one of the leading universities in South Kalimantan. As a university, its driven by an organization to which the letter became one of the important means of communication. But along the way with the increasing number of letters and the development of the organization, it raises some issues that occur, like mail numbering dan searching. By taking advantage of information systems, author tries to do a study to resolve those problems. In this study the authors use an object-oriented approach a method of designing systems with tools such as use case diagrams, activity diagrams, sequence diagrams, and class diagrams. In addition, the authors use a prototyping approach to software development methods. To Support this research data is needed to determine the solution of the problem. Sources of primary data obtained from direct observation (observation) and interviews, while the secondary data obtained from the documents that exist in them.